CHANGES IN SITTING PATTERNS FOLLOWING A RANDOMIZED TRIAL TO REDUCE SEDENTARY TIME IN OBESE OLDER ADULTS. (11th November 2018) - Rosenberg, D; Anderson, M; Renz, A; Matson, T; Lee, A; McClure, J; Kerr, J; Arterburn, D
Abstract: Background: Prolonged sitting is associated with adverse aging-related outcomes. Few interventions have tested whether sitting patterns can be altered in older adults with obesity. We tested the impacts of a sitting reduction intervention (I-STAND) in a pilot randomized controlled trial. Methods: Participants (N = 60, mean age = 68.4, 68% female, 87% white, mean BMI = 36) were randomized to the I-STAND intervention (N = 29) or a healthy living (HL) control group (HL; N = 31) for 12 weeks. I-STAND included 6 health coaching contacts, a Jawbone UP band to cue breaks from sitting, and activPAL feedback on sitting patterns. Sitting patterns included usual bout duration (UBD), breaks from sitting, and periods of sitting for 30+ minutes; these were measured with the thigh-worn activPAL over 7 days at baseline and 12 weeks. Linear regression models estimated group differences in the change from baseline, adjusting for baseline values, wear time, age, sex, and diabetes. Results: I-STAND participants had greater improvements in UBD (mean change from baseline: I-STAND -5.7 vs. HL 0-.9 minutes; p = .06) and the number of periods of sitting for 30 minutes or more (mean change from baseline: I-STAND -1.5 vs. HL 0.9; p = .001) while there was no difference in breaks from sitting. Discussion: A sitting reduction intervention altered sitting patterns by shortening the duration of sitting bouts and reducing prolonged sitting bouts. Further research can determine whether changes in sitting patterns impact aging-related outcomes such as physical function.